A Review: Optimum Conditions for Magnetite Synthesis (Fe3O4) - Tukan, Dominikus Niholan; Rosmainar, Lilis; Kustomo, Kustomo; Rasidah, Rasidah (Jurnal Sains dan Terapan Kimia, 2023)
Magnetite, chemically represented as Fe3O4, is an opaque substance characterized by its black coloration. It possesses a significant saturation magnetization value, denoting a substantial magnetic strength compared to alternative materials. Magnetite (Fe3O4) has significant use across several domains, including its deployment as a catalyst and sensor in the medical sector, such as drug delivery, hyperthermia therapy, and magnetic resonance imaging (MRI). The synthesis of magnetite (Fe3O4) can be achieved using several methodologies, such as solvothermal, sol-gel, solid state, reverse micelle, microwave plasma synthesis, freeze drying, ultrasound irradiation, hydrothermal, and coprecipitation techniques. The co-preparation technique is extensively employed for magnetite synthesis due to its simplicity, ease of usage, and ability to generate magnetic particles at the nanoscale scale without elevated temperatures. The outcome of the coprecipitation process is influenced by various factors such as the nature of the salt, molar ratio, pH level, stirring rate, and reaction temperature. This article aims to examine the impact of many factors, including the salt type, molar ratio, pH level, stirring rate, and reaction temperature, on the production of Magnetite (Fe3O4) through coprecipitation. It was found that Magnetite (Fe3O4) synthesis can produce nanoparticle size material with great magnetic power, namely at pH 8, temperature 70°C, and stirring rate of 10,000 rpm by using FeCl3 and FeCl2 as precursors Fe3+ and Fe2+ with a ratio of 1.5:1 and using precipitating base NH4OH.